Metabolic effects of two high-intensity circuit training protocols: Does sequence matter? - Nuñez, T. P.; Amorim, F. T.; Beltz, N. M.; Mermier, C. M.; Moriarty, T. E.; Nava, R. C.; VanDusseldorp, T. A.; Kravitz, L. (Journal of Exercise Science & Fitness, 2020)
The integration of high-intensity interval training (HIIT) and circuit weight training (CWT) is seamless and practical for meeting recommended exercise guidelines. The purpose of this study was to determine the ideal combination of HIIT and CWT to elicit desired acute cardiorespiratory and metabolic responses in variables such as energy expenditure (EE), oxygen consumption (VO2), heart rate (HR), blood lactate (BLa-), excess post-exercise oxygen consumption (EPOC), rating of perceived exertion (RPE), and enjoyment. Methods: Fourteen trained males (25.7 ± 4.4 yr) completed two exercise protocols matched for volume and recovery periods. On one day, participants performed six HIIT bouts prior to three rounds of a nine exercise CWT protocol (HIC). The second day (separated by = 72 h) consisted of three rounds of three mini-circuits (three exercises per circuit) integrated with three HIIT bouts between the first and second and second and third mini-circuits (TRI). VO2, HR, and EE were monitored throughout both protocols. EPOC for a 20-min duration, [BLa-] (five time points), RPE, and enjoyment were measured post-exercise. Results: Energy expenditure was significantly higher during the HIC compared to the TRI protocol (p = .012), as well as EPOC (p = .034). [BLa-] was significantly greater immediate-, 5min-, 10min- and 20min-post-exercise following HIC as compared to TRI. Mean values for HIC and TRI were similar (p > .05) for HR and RPE. Conclusion: Performing HIIT prior to CWT elicits a higher metabolic perturbation compared to the TRI protocol. Although a significant EE difference was detected between the two trials, the practical difference (~20 kcal) between protocols indicates both protocols are similarly effective for caloric expenditure, metabolic and cardiorespiratory response.